2020
DOI: 10.1111/jcmm.15009
|View full text |Cite
|
Sign up to set email alerts
|

Lobetyolin induces apoptosis of colon cancer cells by inhibiting glutamine metabolism

Abstract: The purpose of the present study was to evaluate the anti‐cancer property of Lobetyolin on colorectal cancer and explore its potential mechanism. Lobetyolin was incubated with HCT‐116 cells in the absence or presence of ASCT2 inhibitor Benser or p53 inhibitor Pifithrin‐α. The levels of glutamine, glutamic acid, α‐ketoglutarate, ATP and GSH were determined to measure the glutamine metabolism. Annexin V‐FITC/PI staining and TUNEL assay were applied to estimate the apoptotic condition. The levels of ASCT2 were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 24 publications
0
38
1
Order By: Relevance
“…The drug blocked the transportation of the tumor suppressor protein p53 to the cell nucleus and thus modulates the expression of several genes implicated in glutamine metabolism and apoptosis of the cancer cells. A profound down-regulation of the ASCT2 gene and protein was observed, resulting in a marked antitumor effect when mice bearing subcutaneous HCT116 tumors were treated with LBT, intraperitoneally at 10-40 mg/kg [61]. The blockade of glutamine metabolism represents an interesting approach to reduce cancer cell growth, by depriving the cells of the fuel which they need to proliferate [64].…”
Section: Anticancer Activity Of Lobetyolinmentioning
confidence: 99%
See 1 more Smart Citation
“…The drug blocked the transportation of the tumor suppressor protein p53 to the cell nucleus and thus modulates the expression of several genes implicated in glutamine metabolism and apoptosis of the cancer cells. A profound down-regulation of the ASCT2 gene and protein was observed, resulting in a marked antitumor effect when mice bearing subcutaneous HCT116 tumors were treated with LBT, intraperitoneally at 10-40 mg/kg [61]. The blockade of glutamine metabolism represents an interesting approach to reduce cancer cell growth, by depriving the cells of the fuel which they need to proliferate [64].…”
Section: Anticancer Activity Of Lobetyolinmentioning
confidence: 99%
“…Several polyacetylene glycosides display anti-inflammatory properties [88][89][90][91][92], such as coreosides A-D which are potent inhibitors of cyclooxygenase-2 [93]. Illustration of the mechanism of action of LBT which was shown to block the transport of the tumor suppressor p53 from the cytoplasm to the nucleus, thereby modulating gene expression and inducing apoptosis of HCT-116 colon cancer cells [61]. Through this p53-dependent mechanism, the drug decreases the content of glutamine and glutamic acid, and down-regulates the expression of the amino acid transporter ASCT2 at the mRNA and proteins lev-els.…”
Section: Other Bioactivities Of Lobetyolin: Antioxidant and Cardiopromentioning
confidence: 99%
“…Ishimaru et al, isolated two new polyacetylene compounds lobetyolin 20 and lobetyol 21 from the hairy roots of Lobelia inflata ( Ishimaru et al, 1991 ) . Recently, He et al studied the effect of lobetyolin on colorectal cancer ( He et al, 2020 ). They found that lobetyolin induces colon cancer cells by inhibiting the ASCT2-mediated glutamine metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Lobetyolin, alkaloids, polysaccharides, and saponins are the major active ingredients in Dangshen, which are responsible for most of the pharmacological functions found in the medicine [34]. Lobetyolin, a general marker compound in Dangshen, has been well reported to exert multiple bioactivities, such as anti-cancer, antiviral, anti-in ammatory, anti-oxidative, mucosal protective, and xanthine oxidase inhibiting properties [35,36].…”
Section: Introductionmentioning
confidence: 99%